The Effect of Reinforcement and Punishment on Employee Performance - Asadullah, ABM; Juhdi, Nurita Binti; Islam, Md Nazrul; Ahmed, Alim Al Ayub; Abdullah, ABM (ABC Journal of Advanced Research, 2019)
There is a direct reciprocal relationship between the employee and the organization. The employee behavior is very important for any organization whose culture greatly influences the former. This study examines the behavioral theories and modern theories that aim at motivating the employee to increase his performance by reinforcements and punishments. Based on the study, an attempt has been made to deeply explore the internal and external factors influencing employee’s behavior. Firstly a case study of external factors on employee behavior has been studied considering the behavioral theory. Secondly, a case study of internal factors on employee behavior have been studied considering modern theory and rejecting the behavioral theory. The results of this investigation from both the cases portray that reinforcement and punishment significantly influence motivation, values, decision making, tackling conflicts and overall performance of the employee.